Pattern of renal and urinary tract disorders in children - Mehraj Uid din Khan,; Yaseer Ahmad Mir,; Touseef Ul Ayoub,; Muzafar Jan, (International Journal of Research in Medical Sciences, 2023)
Background: Pediatricians encounter a wide spectrum of renal and urinary tract ailments in children most of which cause considerable morbidity and mortality in children. Such disorders are seen in children of all age groups starting right from infancy up till adolescence. The aim of our study was to study the prevalence, spectrum and clinical profile of such disorders in children. Methods: This was a hospital based prospective observational study conducted over a period of 12 months from September 2017 to September 2018 at G. B. Pant hospital and Sher-i-Kashmir Institute of Medical Sciences Srinagar. Children presenting with renal and urinary tract disorders between the age group of 1 month and 12 years were prospectively observed and recorded. Results: Total number of patients between age group 1month to 12 years admitted with renal and urinary tract disorders were 197. Majority of patients i.e. 56 (28.4%) were less than one year old. Mean±SD age of patients was 3.9±3.41 years. Fever was the most common complaint present in 78 patients (39.6%). Urinary tract infection was the most common diagnosis in our study comprising of 71 (36%) patients followed by nephrotic syndrome in 39 (19.8%). Other diagnosis were congenital anomalies of kidney and urinary tract- CAKUT (13.2%), acute glomerulonephritis-AGN (10.2%), Acute kidney injury- AKI (9.1%), chronic kidney disease- CKD in 9 (4.6%) and tubular disorders (4.1%). Conclusions: Because of their significant prevalence and impact on the quality of life, renal and urinary tract disorders require prompt diagnosis and management because early detection and treatment improves the morbidity and mortality.